1990
DOI: 10.1002/jcp.1041450117
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tubulin synthesis during the cell cycle in the synchronous plasmodia of Physarum polycephalum

Abstract: Regulation of alpha- and beta-tubulin isotype synthesis during the cell cycle has been studied in the myxomycete Physarum polycephalum, by subjecting synchronous plasmodia to temperature shifts and pharmacological perturbations. Temperature shifts interfered with the regulation of tubulin synthesis. Inhibition of DNA synthesis prevents tubulin degradation after completion of the cell cycle (Ducommun and Wright, Eur. J. Cell Biol., 50:48-55, 1989) but did not perturb the initiation of tubulin synthesis. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Once produced, tubulin proteins tend to be rather stable, with half-lives ranging between 15-50 hrs depending on the cellular model (Caron et al, 1985a;Mooney et al, 1994;Semotok and Lipshitz, 2007). However, this half-life is not absolute but subject to tissue type (Burow et al, 2015), culture substrate (Mooney et al, 1994) and cell-cycle state (Ducommun et al, 1990). Furthermore, tubulins can be recycled for new rounds of polymerisation (Nogales and Wang, 2006), as illustrated also by in vitro studies with purified brain tubulin which can be repeatedly polymerised and depolymerised (e.g.)…”
Section: Regulating Tubulin Availability In Axonsmentioning
confidence: 99%
“…Once produced, tubulin proteins tend to be rather stable, with half-lives ranging between 15-50 hrs depending on the cellular model (Caron et al, 1985a;Mooney et al, 1994;Semotok and Lipshitz, 2007). However, this half-life is not absolute but subject to tissue type (Burow et al, 2015), culture substrate (Mooney et al, 1994) and cell-cycle state (Ducommun et al, 1990). Furthermore, tubulins can be recycled for new rounds of polymerisation (Nogales and Wang, 2006), as illustrated also by in vitro studies with purified brain tubulin which can be repeatedly polymerised and depolymerised (e.g.)…”
Section: Regulating Tubulin Availability In Axonsmentioning
confidence: 99%
“…However, 3H-leucine incorporation data revealed that IC has minimal effect on the synthesis of vimentin and induces a slight decrease in the synthesis rate of a-actin and a-tubulin in OCLE cells. Vimentin synthesis is generally regulated by growth stimulators and thus it is not surprising to observe minimal or no effect of IC on vimentin synthesis by OCLE cells [Traub et al, 1983;Jarvinen, 1990;Tsuru et al, 19901. However, TCLE cells showed significant increase in the rate of a-tubulin synthesis in response to IC [Da Silva and Juliani, 1988;Ducomnun et al, 1990;Fernyhough and Ishii, 1987;Fernyhough et al, 1989;Wheatley et al, 19883. The a-actin and vimentin synthesis of TCLE cells was not significantly altered by IC.…”
Section: Discussionmentioning
confidence: 99%
“…Physarum strains, culture and microscopy Plasmodia (strain CL) were cultured and prepared as described by Ducommun and Wright (1989). Synchronous giant plasmodia (approximately 10cm diameter), grown at 22°C except when stated otherwise, were used before or after the third synchronous mitosis.…”
Section: Methodsmentioning
confidence: 99%
“…This model offers a unique opportunity for following a biochemical event in a single cell during a normal cell cycle or after physical or pharmacological perturbations (Tyson, 1982). Previous studies using this organism have permitted the characterization of the pathways involved in the regulation of tubulin synthesis (Ducommun et al, unpublished data) and degradation (Ducommun and Wright, 1989), and the regulation of thymidine kinase synthesis (Wright and Tollon, 1979, 1989Eon-Gerhardt et al 1981a,6).…”
Section: Introductionmentioning
confidence: 99%